A comparative review of time- and frequency-domain methods for fatigue damage assessment. (October 2022) - Muñiz-Calvente, M.; Álvarez-Vázquez, A.; Pelayo, F.; Aenlle, M.; García-Fernández, N.; Lamela-Rey, M.J.
Abstract: In this paper, a comparative review between time- and frequency-domain methods for fatigue damage assessment is performed. The principal steps of a fatigue study are described in detail: Material Characterization, Definition of the Reference Parameter, Treatment of Loading History, Cycle Counting Algorithm and Damage Model. Furthermore, for each of them the main differences found between the advances made in the time- and frequency-domains are highlighted. As a conclusion, this comparative literature review allows us to identify some important lights and shadows in both approaches: several efforts have been made in the development of advanced material characterization models in S-N field in the time-domain methods, either deterministic or probabilistic, but in the frequency-domain methods only the linear Basquin model is currently used. Also the ongoing discussion about the reference parameter in material characterization (stress, strain, energy, etc.) is not present in the frequency-domain methods, which are mainly based on the stress range. Contrarily, the frequency-domain methods show an advanced treatment of the rainflow histogram with different proposed statistical distributions together with theoretical and analytical relationships between the power spectral density and the expected fatigue damage, leading to a simpler and easier methodology to be applied for fatigue damage assessment than those based on time-domain. Highlights: A comparative review between time- and frequency-domain methods for fatigue damage assessment is performed. The development of material characterization models is more prolific in time-domain. The selection of a suitable reference parameter is an ongoing topic in time-domain. A vast different proposed models to define analytically the rainflow cycle has been formulated in frequency-domain.